Creating Performance Through Development and Quality of Human Resources: Case Study in Pauh Duo District, South Solok Regency - Alfiyon, Findri; Bismark, O. P.; Septaria, Vera; Bismark, Irma Auliyah; Putra, Mandra Adrika (Strata Social and Humanities Studies, 2024)
This research analyzes the influence of human resource development and human resource quality on employee performance in Pauh Duo District, South Solok Regency. This research aims to (1) Understand the description of human resource development and the quality of human resources on employee performance in Pauh Duo District, South Solok Regency, (2) Find out the influence of human resource development on employee performance in Pauh Duo District, South Solok Regency (3) Knowing and analyzing the influence of human resource quality on employee performance in Pauh Duo District, South Solok Regency (4) Knowing and analyzing the influence of human resource development and human resource quality on employee performance in Pauh Duo District, South Solok Regency. This research method is a quantitative descriptive method with data analysis using descriptive analysis and inductive analysis using SPSS for Windows 25. The research results reveal that human resource development has no significant effect on employee performance in Pauh Duo District; the quality of human resources significantly affects employee performance in Pauh Duo District. The development of human resources and the quality of human resources together significantly affect employee performance in Pauh Duo District.